Climate Change, Human Rights and the Response of the African Human Rights System: Focus on the African Commission and the Court on Human and Peoples’ Rights (African Journal of Law and Politics, 2023)
The article argues that the response of the African Human Rights System (AHRS) to climate change is inadequate due to some identified shortcomings and that the Commission and the Court can enhance the climate activism by adopting some innovative measures. Drawing on relevant primary and secondary data, the article underscores the suitability of a human right-based approach to fighting climate change with focus on the measures that the Commission and the Court can adopt in order to enhance the response of the AHRS to climate change. A key recommendation is that the limitations that weaken the response of the AHRS to climate change should be availed through some innovative measures if adopted by the Commission and the Court.